“As Above, So Below”: Promoting reciprocal learning and shared innovation on common-pool resource management between “living laboratories” for sustainable human settlements on Earth and in Space - Esteves, A.; Vermeulen, A.; Nasser, M.; Maranan, D.S: (IASC Commons in Space Virtual Conference, 2021)
This presentation identifies possibilities for reciprocal learning and collaboration on common-pool resource management between two types of “living laboratories” promoting experiential research on sustainable human settlements: ecovillages and outer life support research for space. It is based on a review of output produced by the Global Ecovillage Network and its members, as well as the research projects for space MELiSSA, which focuses on the development of regenerative life support systems, HI-SEAS, geared towards socio-psychological sustainability, and Biosphere 2, which aimed to combine both dimensions. The relevance of this comparative exercise comes from the fact that both ecovillages and life support research for space inquire into how to create conditions for the sustenance of human and non-human life in adverse environments: disrupted terrestrial ecosystems and the life-threatening conditions of outer space. It’s precisely these extreme contexts that force us to rethink accepted relationships between living organisms, humans and their environment, and come up with new configurations. Both categories also aim to promote outreach, lifelong learning, and social and technological innovation about living systems, and have produced considerable output on how to: - Regenerate or (re)create ecosystems through the promotion of closed circular feedback systems including biological and mineral entities; - Support the collective management of resources by promoting well-being and conflict management among participants, as well as incentives for collaboration and reciprocity. This comparative exercise will elaborate on how joint research efforts between ecovillages and life support research projects for space could promote the application of knowledge and innovations from space research to the promotion of sustainable human settlements on Earth, namely in what regards the promotion of food security and circular economies. Equally, it will also elaborate on how the social and ecological technologies developed by ecovillages can contribute to the development of sustainable life support systems in outer space.